Pengembangan Program Inkubator Wirausaha Sosial di Kecamatan Cibungbulang, Kabupaten Bogor - Amiruddin Saleh; Ujang Sehabudin; . Warcito (Institut Pertanian Bogor, 2015)
The action research purposes are: 1) Studying the characteristics of entrepreneurs and business community members of the social entrepreneurial incubator; 2) Review the business partnership and business community through social business incubator; and 3) Increase the motivation for the business and the business community. This research approach is action research. This study uses a descriptive analysis of the target group and the entrepreneurs and business people in the Situ Udik and Cimanggu I Village Cibungbulang Subdistrict, Bogor District. Based on the results of the study showed that: 1) The characteristics of the micro small businessman at Posdaya dominated the productive age with a high school graduate, pick the dependents of 3-4 people; 2) Partnerships undertaken by Posdaya among others, the regional government through BKP5K Bogor, MT Farm, Dompet Dhuafa Livestock, P2MKP KKP, Koperasi Posdaya Indonesia (KPI), IPB, and BRI; and 3) Training and mentoring for small micro business focused on financial management training for families and businesses, packaging design training, mentoring, and technical assistance.